Phthalate exposure increases oxidative stress, early renal injury, and the risk of calcium urolithiasis: A case-control study - Shih-Ting Huang; Tusty-Jiuan Hsieh; Yung-Chin Lee; Chia-Fang Wu; Yi-Chun Tsai; Chu-Chih Chen; Sih-Syuan Li; Jiun-Hung Geng; Yu-Ming Hsu; Che-Wei Chang; Yau-Hsuan Tsau; Shu-Pin Huang; et al. (Ecotoxicology and Environmental Safety, 2024)
Background: Phthalates, ubiquitous in plastics and softening agents, are pervasive in our daily environment. Growing concerns have emerged regarding their potential impact on renal health, particularly due to their propensity to induce oxidative stress. However, the relationship between phthalate exposure and urolithiasis remains poorly understood. This research seeks to explore the connection between phthalate exposure, oxidative stress, and the risk of urolithiasis. Methods: A case-control study involving 285 patients diagnosed with calcium urolithiasis and 594 healthy controls was conducted. Participants completed structured questionnaires and provided urine samples for measuring 10 phthalate metabolites, biomarkers of oxidative stress (malondialdehyde [MDA]) and early renal injury (N-acetyl-beta-D-glucosaminidase [NAG] and albumin/creatinine ratio [ACR]). For subsequent analyses, we utilized distinct categories: the sum of high-molecular-weight phthalate metabolites (∑HMWm), the sum of low-molecular-weight phthalate metabolites (∑LMWm), and the daily intake of di-2-ethylhexyl phthalate (DEHP)(DI_DEHP_5). Results: Stone patients exhibited significantly elevated urinary biomarkers of oxidative stress (MDA) and early renal injury (NAG and ACR), along with higher levels of 9 out of 10 assessed phthalate metabolites compared to normal controls. Within the study population, significant positive associations were found between almost all individual phthalate metabolites and urinary biomarkers of oxidative stress (MDA) as well as early renal injury (NAG and ACR). Logistic regression further confirmed that elevated phthalate levels, including ∑HMWm, ∑LMWm, and DI_DEHP_5, were uniformly associated with an increased risk of oxidative stress, early renal injury, and urolithiasis after adjusting for confounding factors. Conclusions: Our study uncovers a novel association between phthalate exposure and the risk of urolithiasis, underscoring the heightened risk of kidney injury posed by such exposure. Considering the widespread presence of phthalates, regulatory measures and public health interventions are crucial to mitigate phthalate-related nephrotoxicity, while further large-scale longitudinal research is imperative to validate our initial findings and elucidate the underlying mechanisms.